PEMANFAATAN BUDAYA LOKAL SARONEN DALAM PROSES MANAJEMEN PUBLIC RELATIONS - Romadhan, Mohammad Insan (representamen, 2018)
Indonesia is blessed with a variety of tribes and cultures that abound and have a uniquenessuniquenessof diverse between tribes and cultures with one another. based on this the researcherinterested to study about local culture as activity in process of public relations management especiallyat local culture that exist in madura. Researchers interested in researching on the local culture inMadura because madura is one of the typical culture and large enough that exist in Indonesia, besidesmadura is also one of the areas that have cultural diversity, such as one of which is the saronenculture, cow culture, culture sonok cattle and the majority of residents still hold firm local culture inthe area. literature review used is the process of public relations management. This research methodusing qualitative approach, While the type of descriptive research. The results of this study indicatethat the culture has been embedded into various activities in society in Indonesia including the processof public relations management